Steunwerwing in Suid-Afrika - Yolanda Kleynhans (Communicare)
This article focuses on lobbying in South Africa, with special reference to the business sector. Lobbying does indeed take place in South Africa, but is on an ad hoc and unstructured basis when compared with the USA, for example. Most of the persons who perform local lobbying functions do so in a part-time capacity while maintaining major positions as interest-group officials, PROS In companies or as corporate executives. Rather than trying to measure their influence In the policy-making process, the study analyses the level of interest group activity and the lobbying techniques they employ. The institutional foci of lobbying activities are also identified. Conceptual and comparative perspectives are integrated with the empirical data.